ANALYSIS OF FACTORS AFFECTING CONSUMERS IN CHOOSING USING THE ONLINE SHOPPING PLATFORM (SHOPEE) - Nurul Komara Fajrin (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The purpose of the study is to investigate the important factors that affect the decision of the buying on online platform. The sample used in this study were 215 respondents. The data analysis technique that will be used in this research is SEM – PLS. This research is expected to be a reference / consideration for companies, especially E-Commerce companies in making online marketing strategies. This research is expected to be a reference / consideration for companies, especially E-Commerce companies in making online marketing strategies. This research is also expected to contribute to the development of marketing management science, especially online marketing (E-Marketing).